HIV latency potential may be influenced by intra-subtype genetic differences in the viral long-terminal repeat - Doolabh, Deelan Sudhir; Selhorst, Philippe; Williamson, Carolyn; Chopera, Denis; Abrahams, Melissa-Rose (Frontiers in Virology, 2024)
IntroductionElucidation of mechanisms that drive HIV latency is essential to identifying cure strategies. While host mechanisms associated with viral persistence on antiretroviral therapy (ART) have been well studied, less is known about the viral properties that influence latency. The viral promoter element, the 5’ long terminal repeat (LTR), has been shown to affect the number of latently infected cells shortly after infection. Here we investigated the role of subtype C LTR genotypic variation on the establishment of latency in a dual reporter HIV-1 infection model.MethodsThe LTR U3 and R regions from 11 women with acute/early subtype C HIV infection were cloned into the dual reporter pRGH plasmid. Latency potential was calculated based on the expression of fluorescent reporter genes in Jurkat E6–1 cells measured by flow cytometry as the proportion of latent (mCherry +ve cells)/proportion of active (eGFP +ve mCherry +ve cells) infection. Reversal of latency was performed using PMA/Ionomycin stimulation 24 hours before fixing of cells. LTR transcriptional capacity, in the presence and absence of a heterologous subtype C Tat, was measured for the same LTRs cloned into a pGL4.10 luciferase expression vector following transfection of HEK293T cells.ResultsThe majority of proviruses were latent at day 8 post-infection, yet the proportion of latently infected cells varied significantly across participants. We observed a median latent:active infection ratio of 1.79 (range 0.86–2.83) across LTRs with the hierarchy of latency potential remaining consistent across repeat experiments. The median latent:active infection ratio decreased by a median of 3-fold following PMA/Ionomycin stimulation to 0.55 (range 0.46–0.78) indicating that a proportion of latently infected cells could produce viral proteins upon activation. Latency potential did not correlate with LTR transcriptional capacity.ConclusionsWe found intra-subtype level differences in the latency potential of LTRs from South African women independent of their transcriptional capacity, suggesting that HIV-1 LTRs have intrinsic properties that influence the proportion of latently infected cells shortly after infection. The inability to reactivate viral expression in all latently infected cells supports the complex nature of mechanisms driving latency and the need for continued advancements in methods used to study these mechanisms.